Pembelajaran Sentra Pasar Dalam Menstimulasi Perkembangan Sosial Emosional Anak Usia Dini - Lenny Andriani Shanty; Bachtiar Syaiful Bachri; Budi Purwoko (LP. Ma'arif Janggan Magetan, 2023)
This research is aimed to analyze the social and emotional development of young learners. It is necessary for balancing the cognitive aspects. Market day centers can be conducted at an early age in order to give them choices in their life instead of only focusing on cognitive aspects. Besides, it supports social and emotional development. Through this method, the entrepreneurship is introduced in basic level. The social emotional aspects learned in this methods are : (1) being calm during the turn (2) being patient in price agreement(3) accepting the agreement. The quantitative approach was used, namely Quasi Experimental with a nonequivalent control group model. Data collection was conducted through observation and documentation for secondary data. In line with the aim of the research, the result showed that there was a significant difference between the experiment and control group after the treatment. The experiment group became calm during the turn, showed more independence, and respected their peers e.g. price agreement. In conclusion, this method was able to stimulate the social and emotional development in group B Prima Cendekia Kindergarten Islamic School in Grogol, Kediri, Indonesia